Penegakan Hukum Penimbunan Obat Dimasa Pandemi Covid-19 Perspektif Pidana dan Perdagangan - Muhammad Frydo Athala Permadi; Eka Juarsa (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. The phenomenon of hoarding of drugs appears and grabs the attention of the wider community. This is because of its effect on the amount of goods available from stockpiled goods, where some people choose to withhold an item for various reasons. This kind of behavior has a bad effect on fluctuations in the ability to procure and stockpile goods. Writing this thesis aims to overcome legal liability for corporations, as well as law enforcement in tackling the crime of hoarding drugs during the Covid-19 pandemic. In solving the problems that exist in this thesis, the author uses a normative juridical approach or legal research sourced from library materials so that it is also called library law research and is mostly carried out on secondary data in the library. In this case PT. X was found storing hundreds of types of drugs in a warehouse owned by PT. X, one of these drugs is a drug for the treatment of Covid-19